SUBCHRONIC ORAL TOXICITY ASSESSMENTS OF “CAN HUYET VUONG” IN THE EXPERIMENT - Dinh, Thi Thu Hang (Tạp chí Sinh lý học Việt Nam, 2024)
Nowadays, there has been a current trend for researchers to find out new natural ingredients which were safe and still effective in the treatment of diseases. “Can Huyet Vuong” was a herbal-derived product with two main ingredients including Curcuma longa L. (fresh turmeric) and Apis mellifera L. (honey bee) used as an oral medication. So far, the safety of this product has not been reported yet in Vietnam as well as in the world. Thus, this study was designed to assess the subchronic toxicity of “Can Huyet Vuong” in Wistar rats. The method used in this study followed the guidance of World Health Organization in rats with 2 oral doses of 1.8 g/kg b.w/day and 5.4 g/kg b.w/day for 30 days. As a result, “Can Huyet Vuong” did not caused deleterious impacts on general condition, hematological indexes, hepato-renal functions and microscopic images of liver and kidney. Hence, “Can Huyet Vuong” does not appear to produce subchronic toxicities in experimental animals.